Synthesis and characterization of ceria and yttria co-doped zirconia ceramics - Chew, Jonathan You Jie (2019)
Zirconia exists as multiple phases, with monoclinic phase being the most stable in room temperatures. However, with doping of suitable compounds, tetragonal phase and cubic phases can be stabilized at room temperatures. Zirconia has been shown to exhibit shape memory and superelasticity effects in tetragonal form. Unfortunately, bulk zirconia experiences micro-cracking problems which lead to premature fracture. However, recent advances have found that small scaled zirconia samples can exhibit such said effects for multiple cycles without suffering fracture. Due to the importance of such properties in many structural applications, the following study investigates the relationship between sintering conditions and doping concentrations with regards to phase composition and grain size. The study observed that increasing doping concentration of ceria in yttria ceria co-doped zirconia produces more tetragonal phase. Additionally, grain size was observed to increase with sintering temperature. A slight correlation that, increasing doping concentration will also increase grain size was observed. However, the effect of grain size on was minimal compared to sintering temperature. Lastly, the dielectric constant and loss were observed to both follow an increasing trend with the testing temperature regardless of the phase compositions in the ceramics and that the difference in dielectric properties of the phases was insignificant compared to the change in dielectric properties due to temperature.